Understanding ecosystem responses to recurrent marine heatwaves - Emily Lester; Stanley Mastrantonis; Sharyn M. Hickey; Anna Lafratta; Jessica A. Benthuysen; Eben Afrifa-Yamoah; Arani Chandrapavan; Martial Depczynski; Richard D. Evans; David V. Fairclough; Christopher J. Fulton; Marthe Monique Gagnon; et al. (Biological Conservation, 2026)

Exploring distribution, caste-specific seasonality, and winter activity of three invasive wasps (Hymenoptera: Vespidae) in New Zealand using citizen science data - M. Anastasi; M. Bulgarella; J. Anastasi; P. J. Lester (Insectes Sociaux, 2026)
Invasive social wasps are a growing concern in New Zealand, posing both ecological and economic threats. However, gathering large datasets on their phenology and seasonal dynamics can be challenging. In this study, the caste-specific seasonal activity and spatial distribution of three invasive social wasp species ( Polistes dominula , Vespula germanica , and Vespula vulgaris ) in New Zealand were investigated using online citizen science data. The original dataset, sourced from the Global Biodiversity Information Facility (GBIF), contained 3554 observations spanning from 1945 to 2024. Following expert validation, which focused on improving data quality and extracting caste information, a refined dataset of 2028 observations was produced, from 2005 to 2024. Although citizen science data were generally accurate for species identification, expert input substantially improved their utility by providing caste information. Seasonal patterns of reproductive castes aligned with known wasp phenology, with a notable peak in male activity during autumn. Spatially, observations were concentrated in urban and lowland areas, suggesting a potential bias in citizen science data. An ecologically significant finding was the observation of 111 winter-active workers across species, on both islands, and throughout all three winter months. These workers, not confined to urban settings, could indicate potential perennial nesting. The utility of citizen science for ecological monitoring was emphasised in this study, particularly for identifying caste-specific seasonal patterns, such as autumn male activity, which could inform more targeted pest management. Additionally, the findings highlighted the need for further investigation into winter activity and its implications for wasp management.

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Perinatal exposure to delta-9-tetrahydrocannabinol (THC) alters goal-directed behavior and dopamine functioning in wistar rats - Monica S. Carbajal; Rebecca C. Crenshaw; Victoria E. Williams; Laura G. Billings; Chelsea M. Dixon; Deranda B. Lester; Helen J. K. Sable (Psychopharmacology, 2026)
Rationale Cannabis use during 2021pregnancy is common as many pregnant women consider cannabis as a safe way to alleviate symptoms associated with pregnancy because it is “natural”. However, clinical evidence links perinatal cannabis exposure to externalizing behavior in offspring. In preclinical research, most studies focus on exposure to the psychoactive constituent of cannabis, delta-9-tetrahydrocannabinol (THC). THC is lipophilic, allowing it to cross the placental barrier and be secreted in maternal milk, thereby exposing the fetus/neonate. Objective We used operant procedures to measure motivation and impulsivity in adult offspring perinatally exposed to THC. Methods Dams were orally exposed to 0 or 5 mg/kg/day THC daily from 14 days prior to breeding to postnatal day (PND) 14. Differential reinforcement of high rates (DRH) and differential reinforcement of low rates (DRL) of responding tasks were used to examine motivation and impulsive action. We also measured dopamine (DA) functioning in the medial prefrontal cortex (mPFC) and nucleus accumbens (NAc) via in vivo fixed potential amperometry in littermates of rats that completed behavioral testing. Results Perinatal THC exposure had minimal effects on impulsive action measures during DRL 15s. Rather, perinatal THC exposure decreased DRL 15s burst responses and completed trials in both sexes, and reinforcers earned in THC-exposed males. Decreased lever presses during DRH were observed in both sexes perinatally exposed to THC, as well as fewer reinforcers in THC-exposed males. THC exposure did not alter baseline DA release in the NAc or mPFC, but did attenuate the dopaminergic response to cocaine in the NAc. Conclusions These results suggest perinatal exposure to THC can decrease motivation to work for reinforcers during high-effort tasks, that this effect may be more pronounced in males, and that the “amotivational state” resulting from perinatal THC exposure may be due to reinforcer devaluation. Keywords : oral THC, developmental neurotoxicology, amotivational syndrome, mesocorticolimbic dopamine.

Colorectal Cancer in the American Indian and Alaska Native Community: A Holistic Review - Angela R. Monetathchi; William O. Carson; Byron Upshaw; Autumn Lester; Emma Cleary; Alyssa Little; Felina M. Cordova-Marks; Jennifer Erdrich (Journal of Cancer Education, 2026)

Influential drivers in the occupancy and activity of the last megaherbivore from the Northwestern Andean cloud forest of Colombia - Juan Camilo Cepeda-Duque; Valentina López-Velasco; Eduven Arango-Correa; Álex M. López-Barrera; Lester A. Fox-Rosales; Diego J. Lizcano (Mammalian Biology, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Multiple African-origin circulating poliovirus-2 emergences identified in Israel: A reminder of an ongoing global challenge - Neta S. Zuckerman; Hagar Eliyahu; Yaniv Lustig; Danit Sofer; Lester M. Shulman; Leah Weiss; Rinat Vasserman; Reut Gabai; Keren Friedman; Tatyana Kushnir; Lihi Gershon; Ira Aguvaev; et al. (Science of The Total Environment, 2025)

Streptococcus dysgalactiae From Farm‐Raised Channel Catfish in Mississippi, USA, With Notes on Fish‐Associated Group C S. dysgalactiae - Sujita Balami; Lester H. Khoo; Caitlin E. Older; Geoffrey C. Waldbieser; Alvin C. Camus; Taylor I. Heckman; Cynthia C. Ware; Bradley M. Richardson; John P. Hawke; Adrián López‐Porras; Esteban Soto; Craig A. Shoemaker; et al. (Journal of Fish Diseases, 2025)
Lancefield serological group C Streptococcus dysgalactiae (GCSD) is an emerging cause of fish disease worldwide, largely associated with mariculture in Asia. In the United States (US), GCSD had been a pathogen of minimal concern for fish, but recent cases indicate a putative emergence in wild and cultured freshwater fish populations in the Americas. The current study discusses three novel cases of GCSD‐associated streptococcosis in US farm‐raised channel catfish ( Ictalurus punctatus ) occurring in Mississippi, US, in 2022 and 2023. Infected fish presented with pendulous abdomens, red swollen vents, and petechiae on the mouth, fins and ventral lateral abdomen. Clinical isolates were cultured from the kidney and brain and initially confirmed as GCSD by 16S rRNA gene sequencing, followed by phylogenetic analyses using the superoxide dismutase gene ( sod A), 16S/23S internal transcribed spacer region and nine genes within a multilocus sequence analysis scheme for piscine pathogenic Streptococcus . Catfish GCSD were highly homologous to fish strains from published reports from Asia and South America, forming a discrete phylogenetic clade, separate from human and other terrestrial animal isolates. Pairwise genomic comparisons suggest this fish‐associated group does not belong to any currently recognised subspecies and may represent a unique subtype. The broadening host and geographic range of GCSD, coupled with the evidence of a discrete aquatic lineage and recent reports from freshwater fishes in the southeastern US, suggest GCSD is a potential emergent threat to catfish aquaculture in the US.

My place is at risk: spatial assessment of climate risk perceptions along the East Coast of Tasmania and related landscape value associations - Dimuthu Yashodha Jayakody; Vanessa M. Adams; Gretta T. Pecl; Elizabeth Lester (Regional Environmental Change, 2025)
Mapping landscape values alongside climate risk perceptions can show how collective values of the local community and their relationship to the landscape interacts spatially with their risk perception. Such geospatial social data could provide critical insight into local socioecological processes and inform successful place-based climate adaptation planning and risk management outcomes. This study builds on existing landscape value and climate risk participatory mapping methods to identify specific landscape value and risk perception associations. By doing so, prioritisation and targeting of management actions could be informed based on the type of landscape values assigned to a given location, and the perceived vulnerabilities of that place. Our approach combined participatory mapping of landscape values and ‘places at risk’ and follow-up interviews with local community members living along a highly climate vulnerable, coastal region in Tasmania, Australia. Results demonstrated that people’s perceptions of risk were strongly associated with their landscape values. Individuals were more likely to perceive risks and respond to risks that they have experience with (e.g. bushfire); and those that they have directly observed as threats to the landscape values that define their relationship with that place. Thus, risks that are unfamiliar (e.g. flooding and storm surge) were less perceived, and related actions were disregarded. Priority management zones were identified based on the spatial co-occurrence or ‘bundling’ of mapped risks and values. This can inform targeted management strategies in the region based on local context and can also indicate the type of actions needed.

Mariculture Narratives in Climate Change Research and Policy: Alignment, Mismatch, and Opportunities for a Climate‐Resilient Industry - Elizabeth O. Ruff; Lillian M. Bradshaw; Sarah E. Lester (Reviews in Aquaculture, 2025)
Like other sectors of our global food system, marine aquaculture (mariculture) is threatened by a myriad of stressors resulting from a changing climate. Increasing attention has been given to the impact of these stressors on mariculture across a variety of taxonomies and geographies. Alongside this perspective of mariculture as vulnerable to climate change impacts, another narrative has also emerged framing mariculture as a potential mitigation and adaptation measure against climate change. Here, we evaluate the scope and context of these differing narratives across the peer‐reviewed literature and how they are reflected in national mariculture and climate change policy across 31 representative countries. Our literature review identifies a strong research bias toward mariculture being impacted by climate change (75%), with a similar trend present across the small number of relevant policies. While there is broad narrative alignment between science and policy at a global level, in comparing country‐level case studies to their corresponding national policies, we find that five countries have no alignment between research and policy with respect to individual climate change stressors; though most countries have at least some degree of alignment. Strategic governance is a critical tool for responding to climate change and has been shown to play a significant role in shaping the marine aquaculture industry. Our analysis highlights a pattern of science and policy mismatch that could lead to missed opportunities to leverage mariculture's potential as a climate change mitigation and adaptation tool as well as bolster the industry's resilience to climate impacts.

Corrigendum to “Quantitative microbial risk assessment (QMRA) tool for modelling pathogen infection risk to wastewater treatment plant workers” [Water Research volume 260 (2024) 121858] - Ashley Heida; Rasha Maal-Bared; Marc Veillette; Caroline Duchaine; Kelly A. Reynolds; Ahamed Ashraf; Olusola O. Ogunseye; Yoonhee Jung; Lester Shulman; Luisa Ikner; Walter Betancourt; Kerry A. Hamilton; et al. (Water Research, 2025)

Dietary Iron Fortification Did Not Affect the Intestinal Microbiome for Channel Catfish ( Ictalurus punctatus ) Juveniles, but Decreased Their Resistance Against Edwardsiella ictaluri - Fernando Y. Yamamoto; Caitlin E. Older; Lester H. Khoo; Nicholas Romano; Bradley M. Richardson; Brian D. Ott; David J. Wise; Cynthia Ware; Penelope M. Goodman; J. Grant Reifers; Matt J. Griffin (Journal of Fish Diseases, 2025)

Short-wave fadeout on mars: Radio absorption in the dayside martian ionosphere enhanced by solar flares - Y. Harada; B. Sánchez-Cano; M. Lester; A. Ippolito (Icarus, 2025)

Improving wasp control by identifying likely causes of eradication failure - M. W. F. Howse; A. Reason; J. Haywood; P. J. Lester (Journal of Pest Science, 2025)
Studying the efficacy of control methods is paramount to successful management of invasive pests and understanding why some colonies survive is important to improve management practices. Here, the bait Vespex® was used to control invasive wasps across 64 ha of forest in an invaded range near Hanmer Springs, New Zealand. Bait was applied across a standard 50 m by 300 m arrangement and made available for 3 days. Nest mortality rates after 19 days were 29.8%, although nearly all nests were affected with a median overall reduction in nest traffic of 96.5%. The results from logistic regression showed that, all else remaining equal, larger wasp nests, nests further from bait stations, and more isolated nests exhibited lower rates of mortality after baiting. Investigating the change in activity at surviving nests, the results from beta regression suggest that declines in nest traffic were less severe with increasing distance to the nearest bait, but more severe with increasing nest size. These results indicate that while smaller nests are at a higher risk of being killed by the bait, they may not encounter bait as regularly as larger nests. Bait uptake varied considerably across bait stations. Wasp nests were not randomly or uniformly distributed in space, and instead were aggregated across our treatment area, likely due to some aspects of environmental conditions. We suggest further research to be focused on developing an understanding of the drivers of wasp nest development and foraging behaviour, to produce a more flexible baiting procedure that will increase both baiting efficiency and efficacy.

Inferences based on diatom compositions improve estimates of nutrient concentrations in streams - Lester L. Yuan; Richard M. Mitchell; Erik M. Pilgrim; Nathan J. Smucker (Science of The Total Environment, 2024)

Diversity in clinical isolates of Ictalurid herpesvirus 1 ( IcHV1 ) from U.S. farm‐raised catfish and virulence assessment in channel and channel × blue catfish hybrids - Arun Venugopalan; Danielle White; Adrián López‐Porras; Lorelei Ford; Cynthia Ware; Marsha A. Lewis; James M. Steadman; Lester H. Khoo; Bradley Richardson; Charles M. Walker; Todd S. Byars; David J. Wise; et al. (Journal of Fish Diseases, 2024)
Ictalurid herpesvirus 1 (IcHV1) is the most significant viral agent in U.S. catfish aquaculture. Little is known regarding the genetic stability and antigenic variability of IcHV1. Herein, the genetic and antigenic diversity of IcHV1 field isolates was assessed by restriction fragment length polymorphism (RFLP) analysis and serum neutralization assays. RFLP analysis identified two distinct genotypes (IcHV1A and IcHV1B), both discrete from blue catfish alloherpesvirus (BCAHV). Neutralization assays with anti‐IcHV1 monoclonal antibody Mab‐95 indicate shared antigenic determinants for IcHV1A and IcHV1B that are absent from BCAHV, which Mab‐95 did not neutralize. Virulence assessments with representative isolates demonstrate significant differences between isolates within RFLP groups and pooled RFLP group data suggest IcHV1B (pooled survival [mean ± SE]: 58.3% ± 2.6) may be more virulent than IcHV1A (survival: 68.6% ± 2.4). Rechallenges with representative IcHV1A and IcHV1B isolates indicate a cross‐protective effect, with fish surviving initial exposure to IcHV1A or IcHV1B showing robust protection when subsequently re‐exposed to IcHV1A or IcHV1B. This work demonstrated significant differences in virulence between case isolates, identifying two discrete IcHV1 lineages, distinct from BCAHV, with similar virulence in channel and channel × blue catfish hybrids and a cross‐protective effect in catfish surviving exposure to either lineage.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Recent deep-sea nematodes and agglutinated foraminifera select specific grains and bioclasts from their environments: Ecological implications - Sunil K. Das; Raj K. Singh; Mariem Saavedra-Pellitero; Julia Gottschalk; Carlos A. Alvarez Zarikian; Lester Lembke-Jene; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; Chandranath Basak; Anieke Brombacher; et al. (Marine Micropaleontology, 2024)

Quantitative microbial risk assessment (QMRA) tool for modelling pathogen infection risk to wastewater treatment plant workers - Ashley Heida; Rasha Maal-Bared; Marc Veillette; Caroline Duchaine; Kelly A. Reynolds; Ahamed Ashraf; Olusola O. Ogunseye; Yoonhee Jung; Lester Shulman; Luisa Ikner; Walter Betancourt; Kerry A. Hamilton; et al. (Water Research, 2024)

Using DNA metabarcoding to characterize national scale diatom-environment relationships and to develop indicators in streams and rivers of the United States - Nathan J. Smucker; Erik M. Pilgrim; Christopher T. Nietch; Leslie Gains-Germain; Charlie Carpenter; John A. Darling; Lester L. Yuan; Richard M. Mitchell; Amina I. Pollard (Science of The Total Environment, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Internal organs and body tissues of free-swimming whale sharks (Rhincodon typus) imaged using underwater ultrasound - M. G. Meekan; F. Thompson; K. Brooks; R. Matsumoto; K. Murakumo; E. Lester; A. Dove; B. Hopper (Frontiers in Marine Science, 2024)
Ultrasound imaging can be used as an effective tool to measure the reproductive status and condition of sharks. This usually requires restraint of the subject, which is not feasible in the wild when the target species is of conservation concern and very large, as is the case for whale sharks. Our study invoked a behavioral response in free-swimming whale sharks that allowed snorkelers to image internal organs and structures using a submersible ultrasound scanner linked to an iPhone in an underwater housing. We were able to reliably locate and monitor the heart and other internal organs inside the body cavity, structures inside the head, and image skin and muscle in the dorsal surface of the sharks. The technique is evaluated as a means for assessing the condition and reproductive status of free-swimming whale sharks.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Associations between neighborhood characteristics and child well-being before and during the COVID-19 pandemic: A repeated cross-sectional study in the Environmental influences on Child Health Outcomes (ECHO) program - Xueying Zhang; Courtney K. Blackwell; Janet Moore; Shelley H. Liu; Chang Liu; Christopher B. Forrest; Jody Ganiban; Annemarie Stroustrup; Judy L. Aschner; Leonardo Trasande; Sean C.L. Deoni; Amy J. Elliott; et al. (Environmental Research, 2024)

Genetic mapping of two quantitative resistance loci to Venturia nashicola in an interspecific pear family - Kyungho Won; Eu Ddeum Choi; Keumsun Kim; Il Sheob Shin; Seongsig Hong; Cécile Segonzac; Kee Hoon Sohn; Cecilia H. Deng; Lester Brewer; David Chagné; Vincent G. M. Bus (Tree Genetics & Genomes, 2024)

The effects of stem bromelain on the gelation behavior of kappa carrageenan under linear and nonlinear rheological regimes - Wilfred V. Rios; Lester C. Geonzon; Arlyn M. Roque; Ma Roxan B. Abiquibil; Mary Diane A. Pilapil; Mark Adones P. Lingaro; Hyacinth N. Suarez; Raymund Lee Antonio C. Sarmiento; Shingo Matsukawa; Rommel G. Bacabac (Food Hydrocolloids, 2024)

Real-time stored product insect detection and identification using deep learning: System integration and extensibility to mobile platforms - Chetan M. Badgujar; Paul R. Armstrong; Alison R. Gerken; Lester O. Pordesimo; James F. Campbell (Journal of Stored Products Research, 2023)

Effects of nanofertilizer and nano-plant hormone on soil chemical properties and microbial community in two different soil types - John Lester Viscara PIDE; Nolissa Delmo ORGANO; Andre Freire CRUZ; Lilia M. FERNANDO; Lucille C. VILLEGAS; Evelyn F. DELFIN; Michelle Ann Magat CALUBAQUIB; Roselle Estera MADAYAG; Erlinda S. PATERNO (Pedosphere, 2023)

Identifying common stored product insects using automated deep learning methods - Chetan M. Badgujar; Paul R. Armstrong; Alison R. Gerken; Lester O. Pordesimo; James F. Campbell (Journal of Stored Products Research, 2023)

Sociality reduces the probability of eradication success of arthropod pests - M. W. F. Howse; J. Haywood; P. J. Lester (Insectes Sociaux, 2023)
Social insects are successful and globally significant invaders. Compared to ongoing suppression, eradication is seen as an ideal solution and cost effective in the long term. The success of eradication attempts is not guaranteed and identifying key factors that could influence the success of such management programs would be beneficial. In this study, 239 eradication attempts were compiled and analysed to identify why eradication attempts fail, with a focus on how eusociality of the target species impacts eradication success. All else remaining constant, the odds of successful eradication were 79% lower when targeting social species compared to non-social insects. Eradication success was shown to increase when comparing more recent attempts to earlier ones but was found to decrease as the duration of the attempt went on. Eradication attempts that occurred on islands, and those that targeted species with a broader host range, were also associated with increased success. A review of cited reasons for eradication failure highlighted the importance of employing effective control treatments, management, and monitoring systems, as well as garnering adequate social and political support. This study indicates how social insects are particularly challenging to eradicate; it also notes the importance of considering both logistical and biological aspects of any eradication, before initiating eradication attempts.

Environmental surveillance detected type 3 vaccine-derived polioviruses in increasing frequency at multiple sites prior to detection of a poliomyelitis case - Merav Weil; Danit Sofer; Lester M. Shulman; Leah Weiss; Nofar Levi; Irina Aguvaev; Zvi Cohen; Klil Kestin; Rinat Vasserman; Michal Elul; Ilana S. Fratty; Neta S. Zuckerman; et al. (Science of The Total Environment, 2023)

Editorial to the Special Issue: Mixing in Porous Media - Marco Dentz; Daniel R. Lester; Michel F. M. Speetjens (Transport in Porous Media, 2023)

Supercritical water oxidation of phenol and process enhancement with in situ formed Fe2O3 nano catalyst - Ammar Al-Atta; Farooq Sher; Abu Hazafa; Ayesha Zafar; Hafiz M. N. Iqbal; Emina Karahmet; Edward Lester (Environmental Science and Pollution Research, 2022)
During the past few decades, the treatment of hazardous waste and toxic phenolic compounds has become a major issue in the pharmaceutical, gas/oil, dying, and chemical industries. Considering polymerization and oxidation of phenolic compounds, supercritical water oxidation (SCWO) has gained special attention. The present study objective was to synthesize a novel in situ Fe 2 O 3 nano-catalyst in a counter-current mixing reactor by supercritical water oxidation (SCWO) method to evaluate the phenol oxidation and COD reduction at different operation conditions like oxidant ratios and concentrations. Synthesized nano-catalyst was characterized by powder X-ray diffraction (XRD) and transmission electron microscope (TEM). TEM results revealed the maximum average particle size of 26.18 and 16.20 nm for preheated and non-preheated oxidant configuration, respectively. XRD showed the clear peaks of hematite at a 2θ value of 24, 33, 35.5, 49.5, 54, 62, and 64 for both catalysts treated preheated and non-preheated oxidant configurations. The maximum COD reduction and phenol oxidation of about 93.5% and 99.9% were observed at an oxidant ratio of 1.5, 0.75 s, 25 MPa, and 380 °C with a non-preheated H 2 O 2 oxidant, while in situ formed Fe 2 O 3 nano-catalyst showed the maximum phenol oxidation of 99.9% at 0.75 s, 1.5 oxidant ratio, 25 MPa, and 380 °C. Similarly, in situ formed Fe 2 O 3 catalyst presented the highest COD reduction of 97.8% at 40 mM phenol concentration, 1.0 oxidant ratio, 0.75 s residence time, 380 °C, and 25 MPa. It is concluded and recommended that SCWO is a feasible and cost-effective alternative method for the destruction of contaminants in water which showed the complete conversion of phenol within less than 1 s and 1.5 oxidant ratio.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

New data on Henneguya postexilis Minchew, 1977, a parasite of channel catfish Ictalurus punctatus, with notes on resolution of molecular markers for myxozoan phylogeny - Ethan T. Woodyard; Thomas G. Rosser; Justin M. Stilwell; Alvin C. Camus; Lester H. Khoo; Geoffrey Waldbieser; W. Walter Lorenz; Matt. J. Griffin (Systematic Parasitology, 2022)

Asthma and high-intensity interval training have no effect on clustered cardiometabolic risk or arterial stiffness in adolescents - M. A. McNarry; L. Lester; E. A. Ellins; J. P. Halcox; G. Davies; C. O. N. Winn; K. A. Mackintosh (European Journal of Applied Physiology, 2021)
Purpose Cardiometabolic risk, including arterial stiffness, is increasing in youth. Those with asthma are suggested to be particularly at risk of cardiovascular disease. Efficient and effective strategies are required to prevent the atherosclerotic process in youth. The purpose of this study was to investigate the effect of 6 months high-intensity interval training (HIIT) on cardiometabolic risk in youth with and without asthma. Methods 65 adolescents (31 mild asthma; 34 non-asthma) were recruited, 32 (16 asthma) of whom were randomly allocated to receive HIIT three times per week for 6 months. At baseline, mid-intervention, post-intervention and at a 3-month follow-up, anthropometric, metabolic and vascular determinants of cardiometabolic risk were assessed. Following principal component analysis (PCA), linear mixed models were used to assess the influence of asthma, HIIT and their interaction. Results Seven factors were identified which explained 88% of the common variance shared among the parameters. Those with asthma demonstrated lower arterial stiffness factor scores mid-intervention ( P = 0.047) and lower cholesterol factor scores post-intervention ( P = 0.022) but there was no effect of the intervention, or interaction effects, on any PCA-identified factor, at any time-point. HIIT was associated with a lower low-density lipoprotein and diastolic blood pressure at mid-intervention. Discussion Neither arterial stiffness nor clustered cardiometabolic risk are influenced by HIIT in adolescents with or without asthma, despite important changes in blood lipid and pressure profiles. Blood pressure, augmentation and pulse wave velocity should be considered physiologically distinct constructs and as potential markers of cardiovascular health.

Toxin Analysis of Freshwater Cyanobacterial and Marine Harmful Algal Blooms on the West Coast of Florida and Implications for Estuarine Environments - J. S. Metcalf; S. A. Banack; R. A. Wessel; M. Lester; J. G. Pim; J. R. Cassani; P. A. Cox (Neurotoxicity Research, 2021)
Recent marine and freshwater algal and cyanobacterial blooms in Florida have increased public concern and awareness of the risks posed by exposure to these organisms. In 2018, Lake Okeechobee and the Caloosahatchee river, on the west coast of Florida, experienced an extended bloom of Microcystis spp. and a bloom of Karenia brevis in the coastal waters of the Gulf of Mexico that coincided in the Fort Myers area. Samples from the Caloosahatchee at Fort Myers into Pine Island Sound and up to Boca Grande were collected by boat. High concentrations of microcystin-LR were detected in the cyanobacterial bloom along with brevetoxins in the marine samples. Furthermore, β-N-methylamino-L-alanine (BMAA) and isomers N -(2-aminoethyl)glycine (AEG) and 2,4-diaminobuytric acid (DAB) were detected in marine diatoms and dinoflagellates, and cyanobacteria of freshwater origin. High freshwater flows pushed the cyanobacterial bloom to barrier island beaches and Microcystis and microcystins could be detected into the marine environment at a salinity of 41 mS/cm. For comparison, in 2019 collections of Dapis (a new generic segregate from Lyngbya ) mats from Sarasota showed high concentrations of BMAA, suggesting the possibility of long-term exposure of residents to BMAA. The findings highlight the potential for multiple, potentially toxic blooms to co-exist and the possible implications for human and animal health.

Evaluating the Ecological Benefits of Management Actions to Complement Environmental Flows in River Systems - Sam Nicol; J. Angus Webb; Rebecca E. Lester; Marcus Cooling; Paul Brown; Ian Cresswell; Heather M. McGinness; Susan M. Cuddy; Lee J. Baumgartner; Daryl Nielsen; Martin Mallen-Cooper; Danial Stratford (Environmental Management, 2021)

Lagrangian Complexity Persists with Multimodal Flow Forcing in Compressible Porous Systems - M. G. Trefry; D. R. Lester; G. Metcalfe; J. Wu (Transport in Porous Media, 2020)

Investigating the Modulatory Role of Chronological and Biological Age on Performance Predictors in Youth Swimmers - M. A. McNarry; L. Lester; J. Brown; K. A. Mackintosh (Journal of Science in Sport and Exercise, 2020)
Purpose The aim of this study was to determine the modulatory roles of biological maturity and age on the predictors of performance in youth swimmers and their stability over a six-month training cycle. Methods In total, 28 swimmers (10 pre-pubertal [6 boys], 11.1 ± 1.8 years; 18 pubertal [8 boys], 15.2 ± 2.0 years old) and 26 untrained controls (15 pre-pubertal [10 boys], 9.7 ± 1.5 years; 11 pubertal [6 boys], 14.4 ± 0.5 years old) were recruited. At baseline, 3- and 6-months, participants completed an incremental ramp cycle test, isometric handgrip strength test and countermovement jumps, with speed assessed as a measure of performance in swimmers. Principle component analysis (PCA) identified factors that described youth swimmers’ physical profile, with linear mixed models subsequently used to determine their interaction with age and maturity on performance. Results Aerobic fitness and upper body strength were significantly higher in the trained participants, irrespective of maturity status or time-point. Four key factors were identified through PCA (anthropometrics; strength; aerobic capacity; aerobic rate), accounting for 90% of the between parameter variance. Age exerted a widespread influence on swimming performance predictors, influencing all four factors, whilst maturity only influenced the aerobic factors. The key age of divergence was 13 years. Conclusion Overall, the present study found no evidence of a maturational threshold in the aerobic or strength-related response to training in youth. The influence of age on performance predictors suggests that utilising a single or select group of parameters to inform selection and/or talent identification throughout the dynamic processes of growth and maturation should be avoided.

Basal resource quality and energy sources in three habitats of a lowland river ecosystem - Paul J. McInerney; Galen Holt; Rebecca E. Lester; Ross M. Thompson; Barbara Robson; Darren S. Ryder; Nick R. Bond; Darren S. Baldwin; Ben Gawne; Rochelle Petrie (Limnology and Oceanography, 2020)
Understanding energy flow through ecosystems and among sub‐habitats is critical for understanding patterns of biodiversity and ecosystem function. It can also be of considerable applied interest in situations where managing for connectivity among habitats is important for restoring degraded ecosystems. Here, we describe patterns of basal resource quality and identify primary basal energy sources in three habitats—river channels, anabranches and wetlands—of a lowland river floodplain in the Murray River catchment, Australia during a period of disconnected surface flow. We used a combination of stable isotope and fatty acid analyses to determine which basal resources were assimilated by the backswimmer Anisops thienemanni and the Eastern mosquitofish Gambusia holbrooki and assessed food quality across the three habitats. Seston was a primary basal resource for both animals in all three habitats, but was of higher quality within floodplain habitats than in the river channel. Although floodplain seston contained higher concentrations of essential fatty acids, fatty acid profiles of animals from different habitats remained similar. Our research suggests that inundation of floodplains and subsequent reconnection to the river could be valuable to afford riverine animals the opportunity to access high quality resources, but highlights a need to quantitatively assess the transfer of essential fatty acids between trophic levels to determine how much riverine animals are in fact limited by poorer quality food resources. We demonstrate the importance of estimating the quality of organic matter fluxes into food webs, and the potential role of targeted environmental flows to re‐establish high quality energy pathways in riverine ecosystems.

Asymptotic Growth of Whale Sharks Suggests Sex-Specific Life-History Strategies - Mark G. Meekan; Brett M. Taylor; Emily Lester; Luciana C. Ferreira; Ana M. M. Sequeira; Alistair D. M. Dove; Matthew J. Birt; Alex Aspinall; Kim Brooks; Michele Thums (Frontiers in Marine Science, 2020)

Sleep Disordered Breathing in Hypertrophic Cardiomyopathy - Salma I. Patel; Fadi E. Shamoun; Heidi Esser; Sairam Parthasarathy; Michael J. Ackerman; Jeffrey B. Geske; Steve R. Ommen; William T. Love; Virend K. Somers; Anwar A. Chahal; Johan M. Bos; Stephen S. Cha; et al. (Sleep and Vigilance, 2020)

Population genetics of the invasive wasp Vespula germanica in South Africa - J. Eloff; R. Veldtman; M. Bulgarella; P. J. Lester (Insectes Sociaux, 2020)

Viral and fungal pathogens associated with Pneumolaelaps niutirani (Acari: Laelapidae): a mite found in diseased nests of Vespula wasps - A. Felden; J. W. Baty; M. Bulgarella; R. L. Brown; J. Dobelmann; M. A. M. Gruber; O. Quinn; P. J. Lester (Insectes Sociaux, 2020)

Lack of genetic structuring, low effective population sizes and major bottlenecks characterise common and German wasps in New Zealand - Julia M. Schmack; Evan C. Brenton-Rule; Ruan Veldtman; Tom Wenseleers; Jacqueline R. Beggs; Philip J. Lester; Mariana Bulgarella (Biological Invasions, 2019)

The association between mitochondrial genetic variation and reduced colony fitness in an invasive wasp - Jana Dobelmann; Alana Alexander; James W. Baty; Neil J. Gemmell; Monica A. M. Gruber; Oliver Quinn; Tom Wenseleers; Philip J. Lester (Molecular Ecology, 2019)
Despite the mitochondrion's long‐recognized role in energy production, mitochondrial DNA (mtDNA) variation commonly found in natural populations was assumed to be effectively neutral. However, variation in mtDNA has now been increasingly linked to phenotypic variation in life history traits and fitness. We examined whether the relative fitness in native and invasive common wasp ( Vespula vulgaris ) populations in Belgium and New Zealand (NZ), respectively, can be linked to mtDNA variation. Social wasp colonies in NZ were smaller with comparatively fewer queen cells, indicating a reduced relative fitness in the invaded range. Interestingly, queen cells in this population were significantly larger leading to larger queen offspring. By sequencing 1,872 bp of the mitochondrial genome, we determined mitochondrial haplotypes and detected reduced genetic diversity in NZ. Three common haplotypes in NZ frequently produced many queens, whereas the four rare haplotypes produced significantly fewer or no queens. The entire mitochondrial genome for each of these haplotypes was sequenced to identify polymorphisms associated with fitness reduction. We found 16 variable sites; however, no nonsynonymous mutation that was clearly causing impaired mitochondrial function was detected. We discuss how detected variants may alter secondary structures, gene expression or mito‐nuclear interactions, or could be associated with nuclear‐encoded variation. Whatever the ultimate mechanism, we show reduced fitness and mtDNA variation in an invasive wasp population as well as specific mtDNA variants associated with fitness variation within this population. Ours is one of only a few studies that confirm fitness impacts of mtDNA variation in wild nonmodel populations.

Chronic and age-dependent effects of the spongiform neurodegeneration-associated MGRN1 E3 ubiquitin ligase on mitochondrial homeostasis - Teresa M. Gunn; Derek Silvius; Andrew Lester; Britney Gibbs (Mammalian Genome, 2019)

Energy expenditure associated with walking speed and angle of turn in children - Sam G. M. Crossley; Kelly A. Mackintosh; Rory P. Wilson; Leanne J. Lester; Iwan W. Griffiths; Melitta A. McNarry (European Journal of Applied Physiology, 2018)

Selecting and applying indicators of ecosystem collapse for risk assessments - Jessica A. Rowland; Emily Nicholson; Nicholas J. Murray; David A. Keith; Rebecca E. Lester; Lucie M. Bland (Conservation Biology, 2018)
Ongoing ecosystem degradation and transformation are major threats to biodiversity. Measuring ecosystem change toward collapse relies on monitoring indicators that quantify key ecological processes. Yet little guidance is available on selection and use of indicators for ecosystem risk assessment. We reviewed indicator use in ecological studies of ecosystem collapse in marine pelagic and temperate forest ecosystems. We examined indicator‐selection methods, indicator types (geographic distribution, abiotic, biotic), methods of assessing multiple indicators, and temporal quality of time series. We compared how these factors were applied in the ecological studies with how they were applied in risk assessments by using the International Union for Conservation of Nature's Red List of Ecosystems (RLE), for which indicators are used to estimate risk of ecosystem collapse. Ecological studies and RLE assessments rarely reported how indicators were selected, particularly in terrestrial ecosystems. Few ecological studies and RLE assessments quantified ecosystem change based on all 3 indicator types, and indicators types used differed between marine and terrestrial ecosystems. Several studies used indices or multivariate analyses to assess multiple indicators simultaneously, but RLE assessments did not because as RLE guidelines advise against them. Most studies and RLE assessments used time‐series data that spanned at least 30 years, which increases the probability of reliably detecting change. Limited use of indicator‐selection protocols and infrequent use of all 3 indicator types may hamper accurate detection of change. To improve the value of risk assessments for informing policy and management, we recommend using explicit protocols, including conceptual models, to identify and select indicators; a range of indicators spanning distributional, abiotic, and biotic features; indices and multivariate analyses with extreme care until guidelines are developed; time series with sufficient data to increase ability to accurately diagnose directional change; data from multiple sources to support assessments; and explicitly reporting steps in the assessment process.

Dimethyl Fumarate Prevents HIV-Induced Lysosomal Dysfunction and Cathepsin B Release from Macrophages - Lester J. Rosario-Rodríguez; Krystal Colón; Gabriel Borges-Vélez; Karla Negrón; Loyda M. Meléndez (Journal of Neuroimmune Pharmacology, 2018)

Genetic mapping of pear sawfly (Caliroa cerasi) and pear blister mite (Eriophyes pyri) resistance in an interspecific pear family - Lester Brewer; Peter Shaw; Roger Wallis; Peter Alspach; Marlene Aldworth; Carolina Orellana-Torrejon; David Chagné; Vincent G. M. Bus (Tree Genetics & Genomes, 2018)

Co-appearance of OPV and BCG vaccine-derived complications in two infants with severe combined immunodeficiency - Sophia Heiman; Merav Weil; Lester M. Shulman; Amos J. Simon; Atar Lev; Raz Somech; Tali Stauber (Immunologic Research, 2018)

Destruction of Aqueous Phase Organic Pollutants Using Ultraviolet Light-Emitting Diodes and Photocatalysis - Morgan M. Russell; David M. Kempisty; Sushil R. Kanel; Sudarshan Kurwadkar; Seth W. Brittle; Ioana Sizemore; Lester Yaal (Water, Air, & Soil Pollution, 2018)

Complex movement patterns by foraging loggerhead sea turtles outside the breeding season identified using Argos‐linked Fastloc‐Global Positioning System - Antoine M. Dujon; Gail Schofield; Rebecca E. Lester; Kostas Papafitsoros; Graeme C. Hays (Marine Ecology, 2018)
We used Argos‐linked Fastloc‐Global Positioning System (Argos‐linked Fastloc‐GPS) satellite tags to investigate how loggerhead sea turtles use neritic foraging habitats at multiple scales. Out of 24 turtles, six individuals used more than one foraging site, with all sites being separated by >25 km. These six individuals used up to four sites, remaining at each site for a mean of 150 days and returning to the same site a minimum of 52 days later. The other 18 turtles remained in a single site. The area within sites was not used uniformly, with 15 out of 24 turtles exhibiting complex movement patterns within and amongst up to five focal patches, which were typically 0.1–5.0 km apart within a single site. Movements between sites and patches might sometimes have reflected overwintering behaviour; however, similar movement patterns occurred at multiple times of the year, suggesting other factors were also involved. Use of multiple sites and patches might be driven by differences in resource availability, such as food and/or night‐time refuges, competition, or exploratory movement to investigate or locate alternative patches. We confirmed competition via direct visual observations of aggressive interactions between individuals at one foraging patch. Our results illustrate the importance of standardizing data to the same number of locations per day and night to accurately delineate key areas used by turtles or for evidence‐based marine protected area planning.

Fastloc-GPS reveals daytime departure and arrival during long-distance migration and the use of different resting strategies in sea turtles - Antoine M. Dujon; Gail Schofield; Rebecca E. Lester; Nicole Esteban; Graeme C. Hays (Marine Biology, 2017)

A metatranscriptomic survey of the invasive yellow crazy ant, Anoplolepis gracilipes, identifies several potential viral and bacterial pathogens and mutualists - M. Cooling; M. A. M. Gruber; B. D. Hoffmann; A. Sébastien; P. J. Lester (Insectes Sociaux, 2017)

Equine Pulmonary Cryptococcosis: A Comparative Literature Review and Evaluation of Fluconazole Monotherapy - C. J. Secombe; G. D. Lester; M. B. Krockenberger (Mycopathologia, 2017)

Next-generation sequencing revealed dominant fungal populations in collected dust from selected public school classrooms in Metro Manila - Marilen P. Balolong; Leslie Michelle M. Dalmacio; Mark Lester V. Magabo; Diane Nicole L. Sy; Arnold V. Hallare (Aerobiologia, 2017)

Symbiotic bacterial communities in ants are modified by invasion pathway bottlenecks and alter host behavior - Philip J. Lester; Alexandra Sébastien; Andrew V. Suarez; Rafael F. Barbieri; Monica A. M. Gruber (Ecology, 2017)
Biological invasions are a threat to global biodiversity and provide unique opportunities to study ecological processes. Population bottlenecks are a common feature of biological invasions and the severity of these bottlenecks is likely to be compounded as an invasive species spreads from initial invasion sites to additional locations. Despite extensive work on the genetic consequences of bottlenecks, we know little about how they influence microbial communities of the invaders themselves. Due to serial bottlenecks, invasive species may lose microbial symbionts including pathogenic taxa (the enemy release hypothesis) and/or may accumulate natural enemies with increasing time after invasion (the pathogen accumulation and invasive decline hypothesis). We tested these alternate hypotheses by surveying bacterial communities of Argentine ants ( Linepithema humile ). We found evidence for serial symbiont bottlenecks: the bacterial community richness declined over the invasion pathway from Argentina to New Zealand. The abundance of some genera, such as Lactobacillus , also significantly declined over the invasion pathway. Argentine ants from populations in the United States shared the most genera with ants from their native range in Argentina, while New Zealand shared the least (120 vs. 57, respectively). Nine genera were present in all sites around the globe possibly indicating a core group of obligate microbes. In accordance with the pathogen accumulation and invasive decline hypothesis, Argentine ants acquired genera unique to each specific invaded country. The United States had the most unique genera, though even within New Zealand these ants acquired symbionts. In addition to our biogeographic sampling, we administered antibiotics to Argentine ants to determine if changes in the micro‐symbiont community could influence behavior and survival in interspecific interactions. Treatment with the antibiotics spectinomycin and kanamycin only slightly increased Argentine ant interspecific aggression, but this increase significantly decreased survival in interspecific interactions. The survival of the native ant species also decreased when the symbiotic microbial community within Argentine ants was modified by antibiotics. Our work offers support for both the enemy release hypothesis and that invasive species accumulate novel microbial taxa within their invaded range. These changes appear likely to influence invader behavior and survival.

A genetic bottleneck in populations of a New Zealand endemic ant associated with density of an invasive predatory wasp - A. R. Burne; P. A. Ritchie; M. A. M. Gruber; P. J. Lester (Insectes Sociaux, 2017)

Booms, busts and population collapses in invasive ants - Philip J. Lester; Monica A. M. Gruber (Biological Invasions, 2016)

Stock assessment in inland fisheries: a foundation for sustainable use and conservation - K. Lorenzen; I. G. Cowx; R. E. M. Entsua-Mensah; N. P. Lester; J. D. Koehn; R. G. Randall; N. So; S. A. Bonar; D. B. Bunnell; P. Venturelli; S. D. Bower; S. J. Cooke (Reviews in Fish Biology and Fisheries, 2016)

Groundwater cooling of a supercomputer in Perth, Western Australia: hydrogeological simulations and thermal sustainability - Heather A. Sheldon; Peter M. Schaubs; Praveen K. Rachakonda; Michael G. Trefry; Lynn B. Reid; Daniel R. Lester; Guy Metcalfe; Thomas Poulet; Klaus Regenauer-Lieb (Hydrogeology Journal, 2015)

The stinging response of the common wasp (Vespula vulgaris): plasticity and variation in individual aggressiveness - D. Santoro; S. Hartley; D. M. Suckling; P. J. Lester (Insectes Sociaux, 2015)

Nest-based information transfer and foraging activation in the common wasp (Vespula vulgaris) - D. Santoro; S. Hartley; D. M. Suckling; P. J. Lester (Insectes Sociaux, 2015)

lynx1 Supports Neuronal Health in the Mouse Dorsal Striatum During Aging: an Ultrastructural Investigation - Atsuko Kobayashi; Rell L. Parker; Ashley P. Wright; Hajer Brahem; Pauline Ku; Katherine M. Oliver; Andreas Walz; Henry A. Lester; Julie M. Miwa (Journal of Molecular Neuroscience, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

No evidence for cumulative effects in a Dnmt3b hypomorph across multiple generations - Neil A. Youngson; Trevor Epp; Amity R. Roberts; Lucia Daxinger; Alyson Ashe; Edward Huang; Krystal L. Lester; Sarah K. Harten; Graham F. Kay; Timothy Cox; Jacqueline M. Matthews; Suyinn Chong; et al. (Mammalian Genome, 2013)

The conundrum of the yellow crazy ant (Anoplolepis gracilipes) reproductive mode: no evidence for dependent lineage genetic caste determination - M. A. M. Gruber; B. D. Hoffmann; P. A. Ritchie; P. J. Lester (Insectes Sociaux, 2013)

Population decline but increased distribution of an invasive ant genotype on a Pacific atoll - M. A. M. Gruber; A. R. Burne; K. L. Abbott; R. J. Pierce; P. J. Lester (Biological Invasions, 2013)

Removal Processes for Tributyltin During Municipal Wastewater Treatment - M. D. Scrimshaw; D. Hala; A. E. Okiemute; E. Cartmell; J. N. Lester (Water, Air, & Soil Pollution, 2013)

Estrogen suppresses heptatic IκB expression during short-term alcohol exposure - Eric G. Lee; Bethany M. Mickle-Kawar; Lester A. Reinke; Randle M. Gallucci (Inflammation Research, 2012)

A multiplex, internally controlled real-time PCR assay for detection of toxigenic Clostridium difficile and identification of hypervirulent strain 027/ST-1 - A. M. Hoegh; J. B. Nielsen; A. Lester; A. Friis-Møller; K. Schønning (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Prevalence and genetic diversity of three bacterial endosymbionts (Wolbachia, Arsenophonus, and Rhizobiales) associated with the invasive yellow crazy ant (Anoplolepis gracilipes) - A. Sebastien; M. A. M. Gruber; P. J. Lester (Insectes Sociaux, 2012)

Effect of obesity and metabolic syndrome on hypoxic vasodilation - Jacqueline K. Limberg; Trent D. Evans; Gregory M. Blain; David F. Pegelow; Jessica R. Danielson; Marlowe W. Eldridge; Lester T. Proctor; Joshua J. Sebranek; William G. Schrage (European Journal of Applied Physiology, 2012)

The Pharmaceutical Use of Permethrin: Sources and Behavior During Municipal Sewage Treatment - T. Turner; E. Cartmell; J. N. Lester; F. Casse; S. D. W. Comber; M. D. Scrimshaw (Archives of Environmental Contamination and Toxicology, 2011)

Genotype-dependent effects of adolescent nicotine exposure on dopamine functional dynamics in the nucleus accumbens shell in male and female mice: a potential mechanism underlying the gateway effect of nicotine - Price E. Dickson; Tiffany D. Rogers; Deranda B. Lester; Mellessa M. Miller; Shannon G. Matta; Elissa J. Chesler; Dan Goldowitz; Charles D. Blaha; Guy Mittleman (Psychopharmacology, 2011)

An Evaluation of Metal Removal During Wastewater Treatment: The Potential to Achieve More Stringent Final Effluent Standards - D. Ziolko; O. V. Martin; M. D. Scrimshaw; J. N. Lester (Critical Reviews in Environmental Science and Technology, 2011)

A Critical Review of the Formation of Mono- and Dicarboxylated Metabolic Intermediates of Alkylphenol Polyethoxylates during Wastewater Treatment and Their Environmental Significance - T. Y. Chiu; N. Paterakis; E. Cartmell; M. D. Scrimshaw; J. N. Lester (Critical Reviews in Environmental Science and Technology, 2010)

Modelling the Long-Term Fate of Mercury in a Lowland Tidal River. I. Description of Two Finite Segment Models - M. Cristina B. Braga; Jason W. Birkett; John N. Lester; George Shaw (Archives of Environmental Contamination and Toxicology, 2010)

Modelling the Long-Term Fate of Mercury in a Lowland Tidal River. II. Calibration and Comparison of Two Models with Field Data - M. Cristina B. Braga; Jason W. Birkett; George Shaw; John N. Lester (Archives of Environmental Contamination and Toxicology, 2010)

Stock structure of blue threadfin Eleutheronema tetradactylum on the Queensland east coast, as determined by parasites and conventional tagging - M. T. Zischke; T. H. Cribb; D. J. Welch; W. Sawynok; R. J. G. Lester (Journal of Fish Biology, 2009)
Blue threadfin Eleutheronema tetradactylum (Polynemidae) were examined from four areas (Princess Charlotte Bay, Trinity Inlet, Halifax Bay and Upstart Bay) in eastern Queensland covering a distance of c . 950 km of coastline. Parasites were used as biological markers to infer stock structure of E. tetradactylum . Parasites designated as ‘temporary’ biological markers were the copepod Thysanote eleutheronemi , the acanthocephalan Neoechinorhynchus topseyi , the nematode Philometra rajani and hemiurid trematodes. The larval nematodes Anisakis sp. Type 1 and Terranova sp. Type 2; and the larval cestodes Pterobothrium pearsoni and Callitetrarhynchus gracilis were considered ‘permanent’ biological markers. Both univariate and multivariate analyses demonstrated that there was little difference in temporary parasite abundance between the four areas. In contrast, the same analyses revealed that most areas had two or more significant differences in permanent parasite abundance, with the exception of Halifax Bay and Upstart Bay, which were significantly different only in the multivariate analysis. Biological markers predicted that Princess Charlotte Bay and Trinity Inlet consisted of distinct populations, whereas Halifax Bay and Upstart Bay were not clearly differentiated. Tag recapture data supported this hypothesis; the majority of recaptures were within 100 km of the initial tagging location. Geographical movement of E. tetradactylum may be limited due to their biology and ecology, as well as the distances and oceanographic boundaries that separate habitats. Contrary to current management definitions, the stock structure of E. tetradactylum on the east coast of Queensland appears to be geographically differentiated at a small spatial scale.

Nicotine is a Selective Pharmacological Chaperone of Acetylcholine Receptor Number and Stoichiometry. Implications for Drug Discovery - Henry A. Lester; Cheng Xiao; Rahul Srinivasan; Cagdas D. Son; Julie Miwa; Rigo Pantoja; Matthew R. Banghart; Dennis A. Dougherty; Alison M. Goate; Jen C. Wang (The AAPS Journal, 2009)

Dolichodial: A New Aphid Sex Pheromone Component? - Sarah Y. Dewhirst; Michael A. Birkett; Jean D. Fitzgerald; Alex Stewart-Jones; Lester J. Wadhams; Christine M. Woodcock; Jim Hardie; John A. Pickett (Journal of Chemical Ecology, 2008)

Habitat alteration increases invasive fire ant abundance to the detriment of amphibians and reptiles - Brian D. Todd; Betsie B. Rothermel; Robert N. Reed; Thomas M. Luhring; Karen Schlatter; Lester Trenkamp; J. Whitfield Gibbons (Biological Invasions, 2008)

Host Recognition by the Specialist Hoverfly Microdon mutabilis, a Social Parasite of the Ant Formica lemani - Karsten Schönrogge; Emma K. V. Napper; Michael A. Birkett; Christine M. Woodcock; John A. Pickett; Lester J. Wadhams; Jeremy A. Thomas (Journal of Chemical Ecology, 2008)

Community level impacts of an ant invader and food mediated coexistence - M. Sarty; K. L. Abbott; P. J. Lester (Insectes Sociaux, 2007)

CYP19A1 polymorphisms are associated with bone mineral density in Chinese men - Xiumei Hong; Yi-Hsiang Hsu; Henry Terwedow; Lester M. Arguelles; Genfu Tang; Xue Liu; Shanchun Zhang; Xin Xu; Xiping Xu (Human Genetics, 2007)

Illusions of objectivity and a recommendation for reporting data mining results - Manfred Hauben; Lester Reich; Charles M. Gerrits; Muhammad Younus (European Journal of Clinical Pharmacology, 2007)

A decade of the Super Dual Auroral Radar Network (SuperDARN): scientific achievements, new techniques and future directions - G. Chisham; M. Lester; S. E. Milan; M. P. Freeman; W. A. Bristow; A. Grocott; K. A. McWilliams; J. M. Ruohoniemi; T. K. Yeoman; P. L. Dyson; R. A. Greenwald; T. Kikuchi; et al. (Surveys in Geophysics, 2007)

Interactions Between Host-plant Volatiles and the Sex Pheromones of the Bird Cherry-oat Aphid, Rhopalosiphum padi and the Damson-hop Aphid, Phorodon humuli - Tom W. Pope; Colin A. M. Campbell; Jim Hardie; John A. Pickett; Lester J. Wadhams (Journal of Chemical Ecology, 2006)

Data mining in pharmacovigilance: lessons from phantom ships - Manfred Hauben; Lester Reich; Eugène P. Van Puijenbroek; Charles M. Gerrits; Vaishali K. Patadia (European Journal of Clinical Pharmacology, 2006)

Habitat complexity facilitates coexistence in a tropical ant community - M. Sarty; K. L. Abbott; P. J. Lester (Oecologia, 2006)

Immunofluorescent Identification of Melanocytes in Murine Hair Follicles - Dheshnie Govender; Lester M. Davids; Susan H. Kidson (Journal of Molecular Histology, 2006)

Fate and Behavior of Alkylphenols and their Polyethoxylates in an Activated Sludge Plant - Y. K. K. Koh; J. N. Lester; M. D. Scrimshaw (Bulletin of Environmental Contamination and Toxicology, 2005)

Improving the expression of mini-proinsulin in Pichia pastoris - José M. País-Chanfrau; Yuneski García; Lisandra Licor; Vladimir Besada; Lila Castellanos-Serra; Cecilia I. Cabello; Lester Hernández; Manuel Mansur; Liuba Plana; Abdel Hidalgo; Yanet Támbara; María del C. Abrahantes-Pérez; et al. (Biotechnology Letters, 2004)

Identification of Two Sex Pheromone Components of the Potato Aphid, Macrosiphum euphorbiae (Thomas) - Seyed H. Goldansaz; Sarah Dewhirst; Michael A. Birkett; Antony M. Hooper; Diane W. M. Smiley; John A. Pickett; Lester Wadhams; Jeremy N. McNeil (Journal of Chemical Ecology, 2004)

Transgenic Tobacco and Apple Plants Expressing Biotin-binding Proteins are Resistant to two Cosmopolitan Insect Pests, Potato Tuber Moth and Lightbrown Apple Moth, Respectively - Ngaire P. Markwick; Lisa C. Docherty; Margaret M. Phung; Melissa T. Lester; Colleen Murray; Jia-Long Yao; Deepali S. Mitra; Daniel Cohen; Lesley L. Beuning; Sumathi Kutty-Amma; John T. Christeller (Transgenic Research, 2003)

Responses of the Aphids Phorodon humuli and Rhopalosiphum padi to Sex Pheromone Stereochemistry in the Field - Colin A. M. Campbell; Fraser J. Cook; John A. Pickett; Tom W. Pope; Lester J. Wadhams; Christine M. Woodcock (Journal of Chemical Ecology, 2003)

Interaction of Formaldehyde with Soil Humic Substances: Separation by GFC and Characterization by 1 H-NMR Spectroscopy - C. M. Cooke; N. J. Bailey; G. Shaw; J. N. Lester; C. D. Collins (Bulletin of Environmental Contamination and Toxicology, 2003)

Modeling of mini-proinsulin production in Pichia pastoris using the AOX promoter - José M. País; Laura Varas; Jorge Valdés; Cecilia Cabello; Lester Rodríguez; Manuel Mansur (Biotechnology Letters, 2003)

The effect of the cleaner fish Labroides dimidiatus on the capsalid monogenean Benedenia lolo parasite of the labrid fish Hemigymnus melapterus - A. S. Grutter; M. R. Deveney; I. D. Whittington; R. J. G. Lester (Journal of Fish Biology, 2002)
The cleaner fish Labroides dimidiatus affected the pigmented monogenean parasite Benedenia lolo on the fish Hemigymnus melapterus (Labridae) held in aquaria. The effect of cleaner fish varied with the size class of fish; only small fish [ a posteriori size class L S )] exposed to cleaner fish had fewer monogeneans compared with fish not exposed to cleaner fish. The abundance of monogeneans on large fish ( a posteriori size class L S ) was not affected by cleaner fish. The size‐frequency distributions of monogeneans on both size‐classes of H. melapterus were affected by cleaner fish. Fish exposed to cleaner fish had fewer large (>3 mm) and more small ( L. dimidiatus has the potential to control benedeniine monogeneans on captive fish and highlights the importance of taking into account fish size in studies of the effect of cleaner fish on ectoparasites.

Control of Witchweed Striga hermonthica by Intercropping with Desmodium spp., and the Mechanism Defined as Allelopathic - Zeyaur R. Khan; Ahmed Hassanali; William Overholt; Tsanuo M. Khamis; Antony M. Hooper; John A. Pickett; Lester J. Wadhams; Christine M. Woodcock (Journal of Chemical Ecology, 2002)

Avidin Expressed in Transgenic Tobacco Leaves Confers Resistance to Two Noctuid Pests, Helicoverpa Armigera and Spodoptera Litura - Elisabeth P.J. Burgess; Louise A. Malone; John T. Christeller; Melissa T. Lester; Colleen Murray; Bruce A. Philip; Margaret M. Phung; Emma L. Tregidga (Transgenic Research, 2002)

Expression of Biotin-Binding Proteins, Avidin and Streptavidin, in Plant Tissues Using Plant Vacuolar Targeting Sequences - Colleen Murray; Paul W. Sutherland; Margaret M. Phung; Melissa T. Lester; Richelle K. Marshall; John T. Christeller (Transgenic Research, 2002)

Recognition of Complex Odors by Restrained and Free-Flying Honeybees, Apis mellifera - David Laloi; Omar Bailez; Margaret M. Blight; Bernard Roger; Minh-Ha Pham-Delègue; Lester J. Wadhams (Journal of Chemical Ecology, 2000)

Individual Learning Ability and Complex Odor Recognition in the Honey Bee, Apis mellifera L. - David Laloi; Bernard Roger; Margaret M. Blight; Lester J. Wadhams; Minh-Hà Pham-Delègue (Journal of Insect Behavior, 1999)

A Novel Approach for Isolation of Volatile Chemicals Released by Individual Leaves of a Plant in situ - Nicky G. Agelopoulos; Antony M. Hooper; Sangita P. Maniar; John A. Pickett; Lester J. Wadhams (Journal of Chemical Ecology, 1999)

Evaluation of Olfactory Sensing in the Water Industry - R. E. H. Sweeney; M. D. Scrimshaw; G. K. Morse; J. N. Lester (Environmental Monitoring and Assessment, 1998)

Identification of Semiochemicals Released During Aphid Feeding That Attract Parasitoid Aphidius ervi - Yongjun Du; Guy M. Poppy; Wilf Powell; John A. Pickett; Lester J. Wadhams; Christine M. Woodcock (Journal of Chemical Ecology, 1998)

Sex Pheromone Stereochemistry and Purity Affect Field Catches of Male Aphids - Jim Hardie; Lynn Peace; John A. Pickett; Diane W. M. Smiley; J. Robert Storer; Lester J. Wadhams (Journal of Chemical Ecology, 1997)

Deletions in Xq26.3-q27.3 including FMR1 result in a severe phenotype in a male and variable phenotypes in females depending upon the X inactivation pattern - D. J. Wolff; Karen M. Gustashaw; Vickie Zurcher; Lara Ko; Wendy White; Lester Weiss; Daniel L. Van Dyke; Stuart Schwartz; Huntington F. Willard (Human Genetics, 1997)

Chemically mediated associative learning in the host foraging behavior of the aphid parasitoidAphidius ervi (Hymenoptera: Braconidae) - Yongjun Du; Guy M. Poppy; Wilf Powell; Lester J. Wadhams (Journal of Insect Behavior, 1997)

Identification of Floral Volatiles Involved in Recognition of Oilseed Rape Flowers, Brassica napus by Honeybees, Apis mellifera - Margaret M. Blight; Martine Le Métayer; Minh-Hà Pham Delègue; John A. Pickett; Frédéric Marion-Poll; Lester J. Wadhams (Journal of Chemical Ecology, 1997)

Mapping the bovine factor H gene to Chromosome 16 by SSCP analysis - J. L. Williams; D. H. Lester; V. M. Teres; W. Barendse; R. B. Sim; C. J. Soames (Mammalian Genome, 1997)

Toxic element contamination and the occurrence of mercury-resistant bacteria in Hg-Contaminated soil, sediments, and sludges - B. H. Olson; S. M. Cayless; S. Ford; J. N. Lester (Archives of Environmental Contamination and Toxicology, 1991)

Comparative effects of inhaled silica or synthetic graphite dusts on rat alveolar cells - Robert S. Anderson; Sandra M. Thomson; Lester L. Gutshall (Archives of Environmental Contamination and Toxicology, 1989)

Factors affecting the removal of metals during activated sludge wastewater treatment II. The role of mixed liquor biomass - P. S. Lawson; R. M. Sterritt; J. N. Lester (Archives of Environmental Contamination and Toxicology, 1984)

Factors affecting the removal of metals during activated sludge wastewater treatment I. The role of soluble ligands - P. S. Lawson; R. M. Sterritt; J. N. Lester (Archives of Environmental Contamination and Toxicology, 1984)